Akuntabilitas Pemerintahan Desa dalam Pengelolaan Anggaran Pendapatan dan Belanja Desa (APBDes) Tahun 2020 Berdasarkan Permendagri No. 113 Tahun 2014 di Desa Kotah Kecamatan Jrengik Kabupaten Sampang - Rosidah Rosidah; Tituk Diah Widjantie (Ekonomis: Journal of Economics and Business, 2022)
The village income and expenditure budget (APBDes) is a form of accountability by the village government to convey information about all activities carried out by the village government and financed by village funds to the community. The purpose of the research conducted is to determine the accountability of APBDes management in Kotah Village and how the Kotah Village Government is prepared to manage APBDes. This study uses a qualitative type of research, and utilizes informants from the Kotah Village Government Apparatus. This study found that the Kotah Village Government has managed the APBDes in an accountable manner which is in line with Permendagri No. 113 of 2014. The form of Accountability of the Kotah Village Government in accountability of apbdes management report by providing accountability reports to the community is by sticking apbdes management report on the development notice board that has been provided in each hamlet, in the village hall, and at the place of development.